Structural Heart Interventions in the Elderly Population - Devang S. Parikh (Methodist DeBakey Cardiovascular Journal)
Aortic stenosis is the most common valvular heart disease in the elderly population. Since the advent of transcatheter aortic valve implantation (TAVI) in 2002, the clinical indications for this alternative to a surgical replacement have continually expanded. While the treatment of octo- and nonagenarians can present significant challenges, here we present a case of TAVI in an elderly patient. Given her suitable anatomy and active lifestyle that had been limited by her disease state, the patient successfully underwent TAVI 3 weeks later and was discharged post-operative day 1. This case is the basis for providing five key points to remember about the work-up for TAVI for severe aortic stenosis in the elderly population.